On the question of the provenance of the boat shaped fibulae Šmarjeta type in Moravia and Slovakia - Novák, Marek; Trefný, Martin Josef; Felcan, Michal; Cihla, Michal
The boat shaped fibulae of Šmarjeta type are in Northeast Alpine region considered, thanks to the frequent occurrence in the cemeteries of Dolenjska group in Slovenia, as an import from the Southeast Alpine area. However, the gradually increasing number of finds of these fibulae in Northeast Alpine region (Moravia, Slovakia, Austria) indicates the hypothetic question of their local manufacture and distribution. The research of the authors aims to verify this hypothesis focusing on the technical features of individual fibulae (21 pieces from Moravia and 17 pieces from Slovakia) as well as by the XFRF measurement of the composition of the alloy, they are made of. The present paper brings the preliminary results of this research.
Keywords: Early Iron Age